Quiddytyzm i quidditas w metafizyce analitycznej - Lenart, Karol (Filozofia Nauki, 2020)
The paper is a survey of contemporary quidditism, understood as two interrelated metaphysical positions — recombinatorial quidditism, which is an account of the nature of possibilities, and individuation quidditism, which is concerned with the problem of how to individuate properties. I have three aims: to examine the commitments and consequences of both views, to investigate the relationships between them, and to sketch the logic of the dispute between structuralism and quidditism. I explain how these views relate to Ramseyan humility, according to which we cannot know the fundamental structure of the world.